VIRTUAL REALITY - Rogozovs, Niks; Meirāns, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
We deal with history of virtual reality and the principle of virtual reality, as well as the application of virtual reality in selected areas. There was general knowledge of the history of virtual reality, it`s activities, and where these systems are used nowadays. It can be concluded that in the near future, we can expect a great boom in the technology department of virtual reality, which will be able to buy anybody and try to do the same with the virtual world. In 2020, we are expected to see the first progress in virtual reality and to see improvements that can drastically change our daily lives.